The alien - Farber, Erica; Sansevere, John R.; Mayer, Mercer, 1943- (Racine, Wis. : Western Pub. Co., 1995)
LC witnesses the landing of a spaceship, meets an alien, and helps the alien repair his spaceship so that he may return home.
Subtitle on cover: An adventure from outer space.
"A Mercer Mayer Ltd./J.R. Sansevere book."
"A Golden book, New York."
Keywords: Life on other planets -- Juvenile fiction; Unidentified flying objects -- Juvenile fiction; Extraterrestrial beings -- Fiction; Unidentified flying objects -- Fiction; Animals -- Fiction